2016
DOI: 10.7567/jjap.55.1202bb
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between crystal defects and leakage current in β-Ga2O3 Schottky barrier diodes

Abstract: We fabricated Schottky barrier diodes (SBDs) on the entire surface of a ð010Þ β-Ga 2 O 3 single crystal, and investigated the leakage current in both forward and reverse directions. Subsequently, we investigated the distribution of dislocation and void etch pits on the entire surface. The dislocation etch pit density on the surface ranged from <1 ' 10 3 to 6 ' 10 4 , and its average was 1.1 ' 10 4 cm %2 . The void etch pit density on the surface ranged from <5 ' 10 2 to 7 ' 10 3 , and its average was 6 ' 10 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
59
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 84 publications
(62 citation statements)
references
References 25 publications
3
59
0
Order By: Relevance
“…This is a more usual definition than where the current sharply increases, since the latter depends on conduction mechanism) of the large area device was small (∼15 V) and increased with reduced area to 466 V for the smallest diode active area. This is consistent with the larger devices having an increased probability of containing defects that initiate premature breakdown [35]- [41]. Most previously reported diode rectifiers have had areas of less than 10 −3 cm 2 and this effect will not be obvious in that situation [7], [17]- [19].…”
Section: Resultssupporting
confidence: 81%
“…This is a more usual definition than where the current sharply increases, since the latter depends on conduction mechanism) of the large area device was small (∼15 V) and increased with reduced area to 466 V for the smallest diode active area. This is consistent with the larger devices having an increased probability of containing defects that initiate premature breakdown [35]- [41]. Most previously reported diode rectifiers have had areas of less than 10 −3 cm 2 and this effect will not be obvious in that situation [7], [17]- [19].…”
Section: Resultssupporting
confidence: 81%
“…The bulk-limited conductions are dominantly controlled by trap states and trap energy levels in insulator materials, and most types of leakage currents in various devices including a field effect transistor (FET) and a metal/insulator/semiconductor (MIS) junction are dependent on the bulk-limited conduction mechanisms 11 . Recent studies on the relationship between a defect density in dielectric materials and a leakage current have revealed that the dielectric defect density at a contact junction correlates directly with the leakage current through the dielectric film 12 , 13 . It highlights that conventional insulating films can become to transport stably electrical charge carriers without an electrical breakdown by controlling contact junctions or defect densities in the insulator layers.…”
Section: Introductionmentioning
confidence: 99%
“…Our case of 8 μm with doping 4.4 × 10 15 cm −3 has a theoretical breakdown more than an order of magnitude larger than the experimental value. 43,44…”
Section: Resultsmentioning
confidence: 99%
“…[45][46][47][48][49][50][51][52][53][54][55][56][57][58] This is a stringent test of material quality, since large diodes increase the probability of incorporating defects into the active region, degrading reverse breakdown voltage. 37,39,43,45 Lateral devices can achieve high breakdown voltage using large contact separations, but cannot simultaneously achieve high forward current due to the low total conduction thickness. They also have high on-state resistance.…”
mentioning
confidence: 99%